MELAKUKAN MOGOK MENURUT HUKUM DI INDONESIA - I Dewa Ayu Widyani (to-ra, 2018)
A strike is the act of stopping work temporarily jointly by workers in an effort to suppress, with the intention of resuming work after the desired goal is achieved. In Indonesia strike is recognized as a right, which is af rmed in Article 13 of Law no. 14 of 1983 which is then elaborated in article 1 (d) and Article 6 of Law No. 22 of 1957. Legitimate strikes, if strikes are carried out on matters outside the contents of the Labor Agreement (KKB) or in determining the contents of the Labor Agreement (KKB) or in extending the entry into force of the Labor Agree- ment (KKB) and carried out according to procedures that are tired regulated in article 6 of Law No. . 22 of 1957 (as a legal strike / according to the law), which must obtain permission from the Regional Labor Dispute Settle- ment Committee. Keyword : stopping work temporarily; Labor Agreement; legal strike.